The Role of Professionality of Employee Uniform in Creating Customer Satisfaction and Loyalty in Restaurant Context - John, Francy (Auckland University of Technology, 2021)
As a loyal customer can be the brand ambassador of an organisation, service organisations strive to enhance customer loyalty. Customer loyalty in the hospitality context does not only depend on service quality and food quality. There are many other underlying factors that need to be considered by hospitality professionals for building customer loyalty. The primary purpose of this research is to examine the influence of professionality of employee uniform on customer satisfaction and loyalty. In addition, two boundary conditions (service employees’ gender and branded service encounter) were considered to understand the direct and indirect effect of uniform professionality. An online survey was administered for this study with 451 participants recruited from the crowdsourcing platform, Amazon Mturk. Participants were randomly assigned to six different scenarios, in which service employees’ uniform, gender and branded service encounter were manipulated to suit each scenario. Data were analysed using the Statistical Package for Social Science (SPSS) version 27 and the Hayes process macro 3.5. The findings of the study show that the professionality of uniform has a strong impact on customer satisfaction and customer loyalty. In addition, service employees’ perceived competency was found to mediate the effect of uniform professionality on customer satisfaction and loyalty. Service employees’ gender was found to moderate the effect of service employees’ perceived competency on customer satisfaction, while branded service encounters were found to moderate the effect of professionality of employee uniform on customer satisfaction and customer loyalty. The results of the study supplement existing theories on building perception and SERVQUAL. The study has also filled a major gap in the literature on employee uniform and highlighted its importance in creating customer satisfaction and loyalty. The results can be used by hospitality managers as a reference in designing employee uniform and prioritising training employees to provide branded service encounters, by developing standard phrases to communicate brand value to customers.
Keywords: Hospitality; Employee uniform; Employee gender; Branded service encounter; Perceived competence; Customer satisfaction; Customer loyalty; Restaurant; Experiment; Scenario; Multiple studies; Process model